DIFFERENCES AND SIMILARITIES OF RUSSIAN AND FOREIGN LITERATURE - Abdullaev Khusan Abdushukurovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the differences and similarities, the history of the emergence and development of foreign and Russian literature. What distinguishes Russian literature from foreign and vice versa?